2022
DOI: 10.1002/asia.202101388
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Decarboxylative Cyclization of α‐Amino‐Oxy Acids to Access Phenanthridine Derivatives

Abstract: Phenanthridines are a class of useful heterocycles in the field of drug development. In this work, a method via electrochemical decarboxylative cyclization of α‐amino‐oxy acids to access phenanthridine derivatives was developed. This reaction proceeded through iminyl radical formation cascade intramolecular cyclization from readily available materials under environmentally friendly conditions. A wide range of phenanthridine derivatives were obtained in moderate to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 68 publications
(47 reference statements)
0
11
0
Order By: Relevance
“…Based on our experiments and related reports, 14,16,17 a possible mechanism for this electrochemical Minisci reaction is suggested as shown in Scheme 7. TMSN 3 was reduced at the cathode to generate an azide anion I , which was oxidized at the anode to produce the azido radical II .…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Based on our experiments and related reports, 14,16,17 a possible mechanism for this electrochemical Minisci reaction is suggested as shown in Scheme 7. TMSN 3 was reduced at the cathode to generate an azide anion I , which was oxidized at the anode to produce the azido radical II .…”
Section: Resultsmentioning
confidence: 61%
“…15 Developing new synthetic methods under transition-metal- and chemical oxidant-free conditions is one of our research topics. Based on our continuous research on the functionalization of organic compounds under electrochemical conditions, 16 herein, we report an electrochemical Minisci reaction of alcohols with heterocycles via the HAT-driven α-C(sp 3 )–H activation of alcohols (Scheme 1g).…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15][16][17] The electrochemical coupling cyclization of 2-isocyanobiphenyls 8 with amines 7 or the decarboxylative cyclization of α-amino-oxy acids 10 afforded phenanthridines 9 or 11. 12,13 As an important organic fluorine reagent, 14 CF3SO2Na reacted with vinyl azides 12 in MeCN/H2O (10:1) in the presence of LiClO4 under the promotion of electrochemistry to give phenanthridines 13 in up to 63% yields. 15 In acetonitrile, electrochemically promoted cascade cyclization of three components such as isatins 14, alkynes 15 and alcohols 16 delivered 40-81% yields of quinolines 17.…”
Section: Synthesis Of Pyridines Quinolines Phenanthridines and Cinnol...mentioning
confidence: 99%
“…Several works about the formation of thiol radicals by the anodic oxidation for the synthesis of thioethers were developed . Based on our continuous efforts to study the green synthetic methods and radical reactions, herein, we demonstrated a direct cyanation of thiophenols or thiols using the low-toxic trimethylsilyl cyanide (TMSCN) as the cyano source to access the thiocyanates under electrochemical conditions.…”
Section: Introductionmentioning
confidence: 98%